2015
DOI: 10.1104/pp.114.254938
|View full text |Cite
|
Sign up to set email alerts
|

Importin-α-Mediated Nucleolar Localization of Potato Mop-Top Virus TRIPLE GENE BLOCK1 (TGB1) Protein Facilitates Virus Systemic Movement, Whereas TGB1 Self-Interaction Is Required for Cell-to-Cell Movement in Nicotiana benthamiana

Abstract: Recently, it has become evident that nucleolar passage of movement proteins occurs commonly in a number of plant RNA viruses that replicate in the cytoplasm. Systemic movement of Potato mop-top virus (PMTV) involves two viral transport forms represented by a complex of viral RNA and TRIPLE GENE BLOCK1 (TGB1) movement protein and by polar virions that contain the minor coat protein and TGB1 attached to one extremity. The integrity of polar virions ensures the efficient movement of RNA-CP, which encodes the viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…For example, GRV ORF3 contains functional NLS and NoLS sequences; moreover, substitution of the NLS arginine residues with alanine abolishes ORF3 nuclear transit, whereas NoLS leucine mutations interfere with ORF3 nucleolar localization (Kim et al, 2007b). PMTV TGB1 contains two NoLSs responsible for nucleolar localization (Lukhovitskaya et al, 2015). In contrast, the PSLV TGB1 Nterminal domain (NTD) contains a putative NLS (Cluster A, amino acids 116-125) required for nuclear localization and a putative NoLS (Cluster B, amino acids 175-187), and mutations within these regions result in the redistribution of most of the NTD from the nucleolus to the nucleoplasm (Semashko et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, GRV ORF3 contains functional NLS and NoLS sequences; moreover, substitution of the NLS arginine residues with alanine abolishes ORF3 nuclear transit, whereas NoLS leucine mutations interfere with ORF3 nucleolar localization (Kim et al, 2007b). PMTV TGB1 contains two NoLSs responsible for nucleolar localization (Lukhovitskaya et al, 2015). In contrast, the PSLV TGB1 Nterminal domain (NTD) contains a putative NLS (Cluster A, amino acids 116-125) required for nuclear localization and a putative NoLS (Cluster B, amino acids 175-187), and mutations within these regions result in the redistribution of most of the NTD from the nucleolus to the nucleoplasm (Semashko et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…PMTV TGB1 also contains two NoLSs, NoLS-A and NoLS-B. However, the NoLS-A and NoLS-B mutations do not affect viral accumulation in inoculated leaves, and the NoLS-A M mutant and WT virus accumulate to similar levels in the upper leaves, whereas accumulation of the NoLS-B M mutant is only slightly reduced (Lukhovitskaya et al, 2015). Nevertheless, RNA-TGB1 of the double mutant virus, NoLS-AB M , could be detected in the upper leaves, but RNA-CP could not be detected, and PMTV (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations disrupting the structure or function of the ID abolish virus movement (Donald et al, 1997;Solovyev et al, 1999). The recent data of Lukhovitskaya et al (2015) provide additional evidence in favour of our suggestion. They indicated that ID is required for PMTV TGBp1 self-interaction and cell-to-cell movement.…”
Section: V Makarov and Othersmentioning
confidence: 55%
“…NTD deletion is dispensable for these functions. At the same time, PMTV NTD is required for importin-a interaction in plants, nucleolar targeting and long-distance movement (Wright et al, 2010;Lukhovitskaya et al, 2015). In our previous works, we also demonstrated that PSLV NTD is needed for long-distance movement , localization in the nucleus/nucleolus and interaction with two nuclear proteins, i.e.…”
Section: V Makarov and Othersmentioning
confidence: 66%